REFLEKSI KETERAMPILAN GURU PAUD DALAM PEMBELAJARAN TERPADU - Rizka Fitriani (Jurnal Ilmiah Cahaya Paud, 2015)
Childhood is a period of the most important and critical in the growth and development of life. From an early age, children need to be taught character education and life skills in order to be a good quality of human self. A teacher must collaborate professionalism and creativity with the ability to teach and educate young children so that the brand has a balance of life skills to become independent, self-confidence, responsibility and love of self, family, neighborhood and God.Key word: skill, integrated learning.